Effects of mineral supplementation on bio-availability of organic nutrients in commercial dairy herd - GHOSH, T K; HALDAR, S; SARKAR, J (The Indian Journal of Animal Sciences, 2014)
An on-fann trial was conducted for 90 days with 8 crossbred (HF50: Hariana 50) cows of first and second lactation (L1 and L2) to ascertain the effects of mineral supplementation on the bioavailability of organic nutrients in animals. Intakes of DM. OM, CP, crude fibre, ether extracts and lotal carbohydrates did not vary significantly between L1 and L2 either in the pre-supplemental or in the post-supplemental period. Digestibility of DM, ether extracts (P<0.05). OM. CP anti total carbohydrates (P<0.05) increased due to supplementation in both L1 and L2, but the groups did not differ. Milk composition remained unaffected due to supplementation and no difference was found between L1 and L2. Milk yield in L1 declined marginally from 64.2±3.53 kg/animal/week in pre supplemental stage to 61.5±5.47 kg/animal/week in post supplemental stage. This decline in milk yield may be due to the fact that the animals reached the latter half of the lactation as the experiment progressed into the post supplemental stage. In L2 milk yield was fairly constant in both pre and (74.5± 1 15 kg/animal/week) and post supplemental (76.4±0.83 kg/animal/week) stage indicating consistent production performance in second stage of lactation. Intakes of CP, OCP and TDN were below the requirements in pre supplemental stage in both L1 and L2. In the post supplemental stage intakes moved onto higher sides in both the groupsand fulfilled the requirements. It was concluded that within in on-farm feeding practice mineral supplementation could bring about an improvement in the bioavailability of nutrients by augmenting the digestibility of the nutrients.